KOMPARASI TINGKAT SERAPAN SI PADA BEBERAPA JENIS DAN METODE APLIKASI PUPUK SI SERTA IMPLIKASINYA TERHADAP PENINGKATAN PRODUKTIVITAS DAN KETAHANAN ALAMI TANAMAN JAGUNG (ZEA MAYS) - Oktarina Oktarina; M. Iwan Wahyudi; Bagus Tripama (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2021)
The practice of intensive farming systems in corn cultivation with High External Input (HEI) in the form of synthetic chemicals raises problems of ecosystem balance so that national maize productivity remains at 5.1 ton/ha from its potential Yield of 10-12 ton/ha. One of the efforts to increase maize productivity with environmentally friendly principles is the application of silicon fertilization which has the potential to increase the rate of photosynthesis and natural resistance of maize plants. The purpose of this study was to determine the level of Si uptake and accumulation in plant tissues and its implications for corn’s natural resistance, growth, and productivity on several types of Si fertilizers and their application methods. The method to be carried out in this study used an environmental design Splot Plot Design with basic design RCBD with 3 replications and analyzed using Analysis of Variance (ANOVA) followed by 95 % Duncan test (DMRT) if there is a significant difference. The results showed that there was no interaction between the type and method of application with the growth, yield, and natural resistance of plants to pests, but singly affected several observed variables. Silicon fertilization has the potential to increase the uptake rate and content of these elements in plant leaf tissue by application through the roots either leaking or spreading for all types of Si fertilizers although it is not statistically significant. Increasing the Si content in leaf tissue has implications for the relative increase in plant height, especially spray for all types of Si fertilizers, dry weight, number of leaves, leaf area index, and a relative decrease in leaf angle and pest and disease attacks, relatively increasing yield for K2SiO3 and CaSiO3 in all methods. application, as well as the best CaSiO3 in reducing % KA, increasing yield, and % good corncob.